Pembelajaran Bahasa Arab Berbasis Kurikulum Merdeka di Kelas X Madrasah Aliyah Negeri 2 Mojokerto - iftitah (Najah Bestari, 2023)
In Indonesia, in the period of 10 to 15 years there is a learning crisis. In 2020, education in Indonesia was exacerbated again by the Covid-19 virus pandemic, until finally education in Indonesia declined and caused lagging behind in the learning process. In line with this, the Ministry of Education, Culture, Research and Technology, has launched an independent curriculum. The purpose of this study is to find out the independent curriculum material used in the Arabic learning process in grade 10 Madrasah Aliyah Negeri 2 Mojokerto and how the Arabic learning process is based on the independent curriculum. The method used in this study is the qualitative description method. The subjects of this study were class X Arabic teachers, and class X students of Madrasah Aliyah Negeri 2 Mojokerto. Data collection techniques in this study are observation, interviews and documentation. While the technical data analysis is by collecting data, presenting data, and verifying data. The result of this study is that the material contains 4 skills and qowaid, while the implementation is ice breaking, depositing mufrodat every time face-to-face, cooperative learning model, learning reflection and advice and motivation, project-based assignments. Based on the results of the research, it can be stated that the material and process of learning Arabic is based on an independent curriculum. Keywords: Arabic Language Learning, Independent Learning Curriculum, Learning Outcomes.